Hubungan Kondisi Rajungan (Portunus Pelagicus) dan Ekosistem Padang Lamun di Perairan Pulau Poteran Madura - Rifadillah Hisamuddin; Iqbal Wicaksono; Achmad Fachruddin Syah (Universitas Trunojoyo Madura, 2021)
Crab is one of the marine biota which has important economic value, meanwhile, seagrass beds are one of the marine resources that have many benefits for marine life and the coastal environment. This study aims to determine the catch of small crabs and the condition of the seagrass beds in Poteran Island waters. This research uses Sentinel-2A image data downloaded from the earthexplorer.usgs.gov website; Earth Map (RBI) scale 1: 1,000,000, and field data in the form of identification of seagrass objects and water quality. The results showed that the number of female crabs that were caught was more than the male crabs. Based on the width of the carapace, the catch is categorized as unfit to catch. However, based on the weight measurement, the crabs that were caught were categorized as fit to catch. The results of the regression analysis showed that the length and weight of the crab had a fairly good relationship with a regression coefficient of 0.63. The length of the crab is more dominant than the weight. This is indicated by the negative allometric growth pattern (b less than 3). Many crabs are distributed in areas close to seagrass beds. Two types of seagrass were found, namely Enhalus acoroides and Halodule uninervis with rich or healthy conditions. Good water quality is believed to be one of the factors that support the growth of seagrass beds in the waters around Poteran Island.